A simple method for multi-leg loop calculations 2: A general algorithm - Pittau, R. (Computer physics communications, 1998)
The method introduced in a previous paper to simplify the tensorial reduction in multi-leg loop calculations is extended to generic one-loop integrals, with arbitrary internal masses and external momenta.